Closed-end versus open-end: the choice of organizational form - Deli, Daniel N.; Varma, Raj (Journal of Corporate Finance, 2002)
We investigate the choice of organizational form for investment funds. We find that funds that hold less liquid securities with less transparent prices are more likely to be closed-end. The relation is economically meaningful as well as statistically significant. Our results are consistent with Fama and Jensen's [J. Law Econ. 26 (1983a) 327; J. Law Econ. 26 (1983b) 301] prediction that redeemable shares are not efficient when assets are relatively illiquid and asset prices are difficult to observe.